Vagal control of heart rate and cardiac shunts in reptiles: Relation to metabolic state - Wang, T.; Warburton, S.; Abe, Augusto Shinya [UNESP]; Taylor, T. (Cambridge University Press, 2001)
The vagus is clearly of primary importance in the regulation of reptilian cardiorespiratory systems. Vagal control of pulmonary blood flow and cardiac shunts provides reptiles with an additional means of regulating arterial oxygen levels that is not present in endothermic vertebrates (birds and mammals). Within a given species, there exists a clear correlation between withdrawal of vagal tone on the cardiovascular system and elevated metabolic rate. Undisturbed and resting reptiles are normally characterised by high vagal tone, low pulmonary blood flow and large right-left (R-L) cardiac shunts. The low oxygen levels that result from the large R-L shunt may serve to regulate metabolism. However, when metabolism is increased by temperature, exercise or digestion, the R-L cardiac shunt is reduced, which serves to increase oxygen delivery. This response is partially elicit ed by reduction of vagal tone. Interspecies comparisons reveal a similar pattern. Thus, species that are able to sustain the highest metabolic rates possess the highest degree of anatomical ventricular separation and, therefore, less cardiac shunting. It is interesting to note that when cardiac shunts occur in mammals, due for example to developmental defects, they are associated with reduced maximal metabolic rates and impaired exercise tolerance. It appears, therefore, that full separation of ventricular blood flows was a prerequisite for the evolution of high aerobic metabolic rates and exercise stamina in mammals and birds.